Ruthenium-based electrocatalysts for oxygen evolution in acidic media

By dispersing the ruthenium oxychloride species in the manganese oxide support, forming the RuOCl@MnOx electrocatalyst, the problem of insufficient stability in the existing ruthenium-based electrocatalyst in acidic media is solved, and high stability and activity are achieved. It is suitable for Acid oxygen evolution reaction.

CN119497765APending Publication Date: 2025-02-21NANYANG TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380053638.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-15
Filing Date
2023-07-12
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, the ruthenium-based electrocatalyst used for oxygen evolution reaction in acidic media has the problem of insufficient stability, which affects its performance and lifetime in practical applications.

Method used

By dispersing the ruthenium oxychloride species with the general formula RuOCly in the manganese oxide support, a RuOCl@MnOx electrocatalyst is formed, and the stability of the ruthenium-based catalyst is improved by utilizing the acid resistance and oxidation resistance of the MnOx support.

Benefits of technology

High stability and activity in the oxygen evolution reaction in acidic medium are achieved, the overpotential of the electrocatalyst is reduced, and its long-term stability under high current density is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497765A_ABST
    Figure CN119497765A_ABST
Patent Text Reader

Abstract

The present application provides a ruthenium-based electrocatalyst for oxygen evolution in an acidic medium. The ruthenium-based electrocatalyst includes a ruthenium oxychloride species having the general formula RuOCly, the ruthenium oxychloride species being dispersed in a manganese oxide support, the manganese oxide support having the general formula MnOx. The invention also provides a manufacturing method of the ruthenium-based electrocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority to Singapore application number 10202250487W filed on July 15, 2022, the entire contents of which are incorporated herein by reference for all purposes. Technical Field

[0003] The present application relates to a ruthenium-based electrocatalyst. Specifically, the present application relates to a ruthenium-based electrocatalyst for oxygen evolution in an acidic medium and a method for manufacturing the ruthenium-based electrocatalyst. Background Art

[0004] Hydrogen fuel is considered as a promising energy carrier to replace traditional fossil fuels for sustainable energy in the future. A clean and sustainable hydrogen economy can only be truly established when hydrogen is produced by water splitting technology driven by renewable energy sources such as wind and solar energy. Proton-exchange membrane (PEM) electrolysis for hydrogen production has shown many unique advantages over alkaline water electrolysis, including higher current density, higher purity of pressurized hydrogen, more compact and portable electrolyzer systems, and importantly, better compatibility with intermittent / non-continuous renewable energy. However, the large-scale application of PEM electrolyzers has been limited by their precious catalysts, especially the lack of durable, efficient and cost-effective electrocatalysts for oxygen evolution reaction (OER) in strongly acidic media. Currently, precious metal ruthenium / iridium-based compounds are commercial electrocatalysts for acidic oxygen evolution reaction. Compared with iridium oxide, ruthenium oxide (RuO2) has higher oxygen evolution reaction activity and lower cost, but has poorer stability than iridium oxide.

[0005] Since the reported stability of ruthenium-based catalysts is far from practical application, great efforts have been invested in exploring methods to improve both the stability and activity of ruthenium-based oxygen evolution reaction catalysts. Many methods focus on structural modification of crystals or crystalline phases and doping or compounding based on ruthenium oxide itself, which inevitably introduces ruthenium oxide (RuO2) crystals into the catalyst, which leads to oxidative degradation under acidic conditions and at lower anodic potentials.

[0006] It would therefore be desirable to provide a ruthenium-based electrocatalyst and method that seeks to address at least one of the above-mentioned problems, or at least provide an alternative. Summary of the invention

[0007] According to a first aspect, the present disclosure provides a ruthenium-based electrocatalyst. The ruthenium-based electrocatalyst comprises a ruthenium-based electrocatalyst having the general formula RuOCl y A ruthenium oxychloride species is dispersed in a manganese oxide support having a general formula of MnO x .

[0008] In some embodiments, the ruthenium-based electrocatalyst further comprises a substrate, wherein the ruthenium-based electrocatalyst is disposed on at least one surface of the substrate.

[0009] According to a second aspect, the present disclosure provides a method for manufacturing a ruthenium-based electrocatalyst. The method comprises: heating a substrate; applying a precursor solution containing a chloride salt of ruthenium and a nitrate salt of manganese to the substrate; and heating the precursor solution and the substrate to obtain a ruthenium-based electrocatalyst, wherein the ruthenium-based electrocatalyst comprises a catalyst having a general formula of RuOCl y The ruthenium oxychloride species is dispersed in a manganese oxide support having a general formula of MnO x . BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Various embodiments of the present disclosure are described in the following detailed description with reference to the following drawings:

[0011] Figure 1 is a flow chart of an example method of making a ruthenium-based electrocatalyst according to some embodiments described herein.

[0012] Figure 2 According to an embodiment of the present disclosure, active ruthenium oxychloride (RuOCl y ) species dispersed in manganese oxide (MnO x ) Schematic diagram of the oxygen evolution reaction (OER) on the electrocatalyst obtained in the support.

[0013] Figure 3 (A) RuOCl@MnO x Sample, (B) MnO x X-ray diffraction (XRD) spectra of (C) RuOCl sample, (D) glass sample and (E) pure RuO2 sample.

[0014] Figure 4 (A) RuOCl@MnO x Sample, (B) MnO x Raman spectra of (A) sample and (C) RuOCl sample.

[0015] Figure 5 (A) RuOCl@MnO x , (B) RuOCl and (C) MnO x The full spectra of X-ray photoelectron spectroscopy (XPS).

[0016] Figure 6 (A) RuOCl@MnO x and (B) XPS spectrum of Ru 3p of RuOCl.

[0017] Figure 7 It is shown that RuOCl@MnO x XPS spectrum of Ru 3d / C 1s, “Sat.” represents the satellite peak of Ru 3d.

[0018] Figure 8 (A) RuOCl@MnO x and (B) XPS spectrum of Cl 2p of RuOCl.

[0019] Fig. 9 (A) RuOCl@MnO x and (B) MnO x XPS spectrum of O 1s.

[0020] Fig.10 (A) RuOCl@MnO x and (B) MnO x XPS spectrum of Mn 2p state.

[0021] Fig.11 The atomic ratios obtained from XPS results are shown, where the RuOCl@MnO x and RuOCl samples, the atomic concentration is normalized to the concentration of Ru, and in MnO x In the sample, the atomic concentration is normalized to the concentration of Mn.

[0022] Figure 12 (a) shows (A) RuOCl@MnO on carbon fiber paper x (B)RuOCl@MnO xRu K-edge normalized X-ray absorption near edge spectroscopy spectra (XANES spectra) of (A) RuOCl@MnO on carbon fiber paper, (C) RuO2 standard sample, (D) RuCl3 standard sample, and (E) Ruthenium foil. x , (B) RuOCl@MnO x Figure 12(c) shows the derivative normalized XANES spectra of (A) RuOCl@MnO on carbon fiber paper. x (B)RuOCl@MnO x Normalized XANES spectra of Mn K-edge of (A) RuOCl@MnO on carbon fiber paper, (C) MnO2 standard sample, (D) manganese (III) oxide (Mn2O3) standard sample, (E) MnCl2·xH2O standard sample, and (F) manganese foil. x (B)RuOCl@MnO x Derivative normalized XANES spectra of powder, (C) MnO2 standard sample, (D) manganese (III) oxide (Mn2O3) standard sample, (E) MnCl2·xH2O standard sample and (F) manganese foil. Figure 12 (e) and (f) show the standard driven linear regression of the ruthenium sample and the manganese sample, respectively.

[0023] Figure 13 (a) is RuOCl@MnO x Figure 13 (b) shows RuOCl@MnO x The selected area electron diffraction (SAED) pattern shows weak diffraction rings corresponding to the (222), (411), (521) and (622) planes of Mn2O3.

[0024] Figure 13(c) shows that RuOCl@MnO xAberration-Corrected High-Angle Annular Dark Field - Scanning Transmission Electron Microscopy (AC HAADF-STEM) image. Figure 13 (d) shows a High-Angle Annular Dark Field - Scanning Transmission Electron Microscopy (HAADF-STEM) image, and Figures 13 (e), 13 (f), 13 (g), and 13 (h) show the corresponding Scanning Transmission Electron Microscopy - Energy Dispersive X-ray Spectroscopy (STEM-EDS) mappings of Ru, Cl, O, and Mn, respectively.

[0025] Figure 13 (i) shows (A) RuOCl@MnO x , (B) RuO2 standard sample, (C) RuCl3 standard sample and (D) RuK edge of ruthenium foil. Figure 13 (j) shows (A) RuOCl@MnO x (A) RuOCl@MnO on powder and (B) carbon fiber paper (CFP) x , (C) FT-EXAFS spectra of Mn K-edge of MnCl2 standard sample and (D) manganese foil.

[0026] Figure 13(k) shows that RuOCl@MnO x Figure 13 (l) shows the atomic ratios obtained from the energy dispersive spectrometer (EDS) results, where (A) RuOCl@MnO x The atomic concentrations are normalized to the concentration of Ru in (A) RuOCl and (C) MnO x In the figure, the atomic concentration is normalized to the concentration of Mn.

[0027] Fig.14 (a) RuOCl@MnO x and (b) transmission electron microscopy (TEM) images of RuOCl and (c) RuOCl@MnO x The electron energy loss spectroscopy (EELS) of the sample and (d) RuOCl sample is shown.

[0028] Fig.15 (a) RuOCl@MnO x (b)MnO x and (c) Scanning Electron Microscopy (SEM) image of RuOCl.

[0029] Figure 16(a) shows that RuOCl@MnO x Scanning Electron Microscopy - Energy Dispersive Spectrometer (SEM-EDS) image of the sample and SEM-EDS distribution diagram of Ru Lα, Cl Kα, O Kα and Mn Kα.

[0030] FIG16( b ) shows the SEM-EDS image of the RuOCl sample and the SEM-EDS distribution diagrams of Ru Lα, Cl Kα, O Kα, and C Kα.

[0031] Figure 17 (a) shows the current density of 10 mA cm⁻². x 、(B)RuOCl、(C)MnO x , (D) RuO2|1.05@CFP, (E) RuO2|0.15@CFP, (F) RuOCl / MnO x 、(G)RuO2 / MnO x (a) and (b) chronopotentiometry curves of carbon fiber paper (CFP). The inset is a zoomed-in curve within 25 h. x At 100 mA cm -2 , 300 mA cm -2 and 500 mA cm -2Figure 17(c) is a diagram showing the chronopotentiometry curves without iR correction at a current density of (A) RuOCl@MnO x (B)MnO x , (C) Illustrations of the polarization curves of RuO2|0.15@CFP and (D) RuO2|1.05@CFP.

[0032] Fig.18 It is shown that RuOCl@MnO x , RuO2|1.05@CFP, RuO2|0.15@CFP and MnO x At 10 mA cm -2 The overpotential (η 10 ) and RuOCl@MnO x , RuO2|1.05@CFP and RuO2|0.15@CFP at an overpotential of 300 mV.

[0033] Fig.19 Figure 2 shows the linear sweep voltammetry (LSV) curves of (1) the first, (2) the second, and (3) the third tests of RuOCl and (A) RuOCl@MnO x Graphical representation of the LSV curve.

[0034] FIG20( a ) is a diagram showing LSV curves of RuO 2 |x@CFP (x=(i) 0.15, (ii) 0.3, (iii) 0.45, (iv) 0.6, (v) 0.75, (vi) 0.9, (vii) 1.05). FIG20( b ) is a TEM image of commercially available RuO 2 .

[0035] Fig.21 It shows that (A) RuOCl@MnO x , (B) Graphical representation of the mass activity of RuO2|0.15@CFP and (C) RuO2|1.05@CFP.

[0036] Fig. 22 (A) RuOCl@MnO x Tafel plots of (A) RuO2|1.05@CFP (43 mV dec⁻¹), (B) RuO2|1.05@CFP (48 mV dec⁻¹), and (C) RuO2|0.15@CFP (53 mV dec⁻¹).

[0037] Fig.23 It is shown that RuOCl@MnO xSEM images before (ac) and after (df) 280 h stability testing, with increasing magnification from left to right.

[0038] Fig.24 The initial RuOCl@MnO x , RuOCl@MnO after 280 hours stability test x And the X-ray diffraction spectrum of carbon fiber paper (CFP).

[0039] Fig.25 is 10 mA cm -2 Next, RuOCl@MnO after 280 hours of stability test x HRTEM image of .

[0040] Fig.26 (a) shows RuOCl@MnO x Raman spectra before (A) and after (B) the 280-hour stability test. Fig.26 (b) shows (A) the initial RuOCl@MnO x , (B) RuOCl@MnO after 48 hours stability test x and (C) RuOCl@MnO after 280 h stability test x XPS spectrum of Ru 3p state. Fig.26 (c) shows (A) the initial RuOCl@MnO x , (B) RuOCl@MnO after 48 hours stability test x , Normalized Ru K-edge XANES spectra of (C) ruthenium foil, (D) RuCl3 standard sample and (E) RuO2 standard sample. Fig.26 (d) shows (A) the initial RuOCl@MnO x , (B) RuOCl@MnO after 48 hours stability test x , (C) Normalized Mn K-edge XANES spectra of MnCl2·xH2O standard sample, (D) Mn2O3 standard sample and (E) MnO2 standard sample. Fig.26 (e) and (f) show (A) initial RuOCl@MnO x , (B) RuOCl@MnO after 48 hours stability test x and (C) RuOCl@MnO after 280 h stability test x XPS spectra of Mn 2p state and Cl 2p state.

[0041] Figure 27 (a) and (b) show (A) the initial RuOCl@MnO x, (B) RuOCl@MnO after 48 hours stability test x and (C) RuOCl@MnO after 280 h stability test x XPS spectra of O 1s and C 1s / Ru 3d states. The C 1s peak has been corrected to 284.8 eV.

[0042] Fig.28 Shown (ac) at 100 mA cm -2 RuOCl@MnO after 200 hours of stability test x , (df) at 300 mA cm -2 RuOCl@MnO after 100 hours of stability test x and (gi) at 500 mA cm -2 RuOCl@MnO after 50 hours of stability test x SEM images and SEM-EDS full element distribution maps (scale bar: 1 μm).

[0043] Fig.29 It is shown that RuOCl@MnO x (a) At 100 mA cm -2 After 200 hours of stability testing, (b) at 300 mAcm -2 After 100 h stability test at (c) 500 mA cm -2 Below is the HRTEM image after 50 hours of stability testing.

[0044] Fig.30 (A) Initial RuOCl@MnO x and (B) at 100 mA cm -2 RuOCl@MnO after 200 hours of stability test x , (C) at 300 mA cm -2 RuOCl@MnO after 100 hours of stability test x and (D) at 500 mA cm -2 RuOCl@MnO after 50 hours of stability test x Raman spectrum.

[0045] Figure 31 shows (A) the initial RuOCl@MnO x and (B) at 100 mA cm -2 RuOCl@MnO after 200 hours of stability test x , (C) at 300 mA cm -2RuOCl@MnO after 100 hours of stability test x and (D) at 500 mA cm -2 RuOCl@MnO after 50 hours of stability test x XPS spectra of (a) Ru 3p state, (b) Mn 2p state, and (c) O 1s state.

[0046] Fig.32 The Pourbaix diagram of the 89-11% Mn-Ru system in aqueous solution is based on the reported method (Toma, FM et al., "Mechanistic study of chemical and photochemical transformations of bismuth vanadate photoanode", Nature Communications, Vol. 7, 12012 (2016)), where the manganese and ruthenium ion concentrations are assumed to be 10 -8 mol.kg⁻¹. Here, RuO4(aq) is used to describe the state of ruthenium at a higher positive potential. Multiple regions are labeled to represent the following multiple stable phases: A-MnO4-+RuO4(aq); B-Mn 3+ +RuO4(aq);C-Mn 2+ +RuO4(aq);D-MnO2(s)+RuO4(aq);E-Mn 2+ +Ru(OH)2 2+ ; F-Mn 2+ +RuO2(s);G-Mn2O3(s)+RuO4(aq);H-MnO4 2- +RuO4(aq);I-Mn2O3(s)+RuO2(s);J-Mn 2+ +Ru(s);K-Mn3O4(s)+RuO2(s);L-MnOH + +RuO2(s);M-Mn(OH)3-+RuO2(s);N-MnOH + +Ru(s);O-Mn(OH)3-+Ru(s);P-Mn 2+ +MnRu3(s);Q-MnOH + +MnRu3(s); R-Mn(OH)3-+MnRu3(s); S-Mn(s)+MnRu3(s).

[0047] FIG33(a) is a graphical representation of slow linear sweep voltammetry (LSV) curves without iR correction extending to higher positive potentials. FIG33(b) is a graphical representation of the formation energy and (010) surface energy of bulk phases of RuO2, Mn2O3, and Mn2O3Ru. FIG33(c) is a graphical representation of free energy curves for oxygen evolution reaction on different surfaces, such as (A) Ru2 site on Mn2O3Ru(110), (B) RuO2, (C) Ru1 site on Mn2O3Ru(110) surface, and (D) Mn site on Mn2O3Ru(110), where the theoretical overpotentials are 0.75 V, 0.99 V, 1.11 V, and 1.32 V, respectively. (E) is an ideal catalyst. The unit of Gibbs free energy is electron volt (eV). FIG. 33( d ) shows the geometric structures and intermediates for oxygen evolution reaction on different surfaces, where Ru atoms, Mn atoms, O atoms, and H atoms are shown.

[0048] Fig.34 The simulation model established in bulk form after structural optimization of RuO2, Mn2O3 and Mn2O3Ru and the calculated bond lengths are shown, wherein Ru atoms, O atoms and Mn atoms are shown.

[0049] Fig.35 Comparison of the structural units of RuO2, Ru1 in Mn2O3Ru, and Ru2 in Mn2O3Ru on the (110) surface without vacancy defects (top) and with vacancy defects (bottom). DETAILED DESCRIPTION

[0050] The following is described in detail in conjunction with the accompanying drawings, in which details and embodiments of the present disclosure are shown for illustrative purposes. Features described in the context of one embodiment may be correspondingly applicable to the same or similar features in other embodiments, even if not explicitly described in other embodiments. Applications and / or combinations and / or substitutions described for features in the context of one embodiment may be correspondingly applicable to the same or similar features in other embodiments.

[0051] In the context of various embodiments, the articles “a,” “an,” and “the” used with respect to a feature or element include reference to one or more of the features or elements.

[0052] In the context of various embodiments, the term "about" or "approximately" as applied to a numerical value encompasses the exact value and a reasonable difference commonly understood in the relevant technical field, for example, within 10% of the specified value.

[0053] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0054] As used herein, “comprising” means including but not limited to whatever follows the word “comprising.” Thus, the use of the term “comprising” indicates that the listed elements are required or mandatory, but other elements are optional and may or may not be present.

[0055] As used herein, “consisting of” means including and limited to whatever is interposed between the phrase “consisting of.” Thus, the use of the phrase “consisting of” means that the listed elements are required or mandatory, and that no other elements are present.

[0056] Detailed description of various embodiments will be described below with reference to the accompanying drawings.

[0057] The present disclosure relates to an electrocatalyst. The electrocatalyst belongs to the fields of electrochemistry, material synthesis, catalysis, water electrolysis, hydrogen energy, batteries, etc. Specifically, the present disclosure relates to a ruthenium-based electrocatalyst. The ruthenium-based electrocatalyst includes a ruthenium-based electrocatalyst having the general formula RuOCl y The ruthenium oxychloride species is dispersed in a manganese oxide support having a general formula of MnO x In various embodiments, y represents a number between 0.2 and 1.6, and x represents a number between 1.7 and 1.8.

[0058] In various embodiments, the ruthenium-based electrocatalyst is referred to as RuOCl@MnO x The “RuOCl@MnO x The term "manganese oxide" refers to a x ) in the support y ) species of ruthenium-based electrocatalysts, among which ruthenium oxychloride (RuOCl y ) species and manganese oxide (MnO x ) Chemical bonds are formed between the supports.

[0059] In various embodiments, RuOCl y With MnO x The molar ratio is 1:11.1 or 1:7.8.

[0060] In various embodiments, the ratio of Ru:Cl:O in RuOCl is 1:0.4:2.4 or 1:0.2:2.1.

[0061] In various embodiments, MnO x The ratio of Mn:O in the alloy is 1:1.7 or 1:1.8.

[0062] In various embodiments, RuOCl@MnO xThe ratio of Ru:Cl:O:Mn is 1:1.6:18.0:11.1.

[0063] In one embodiment, the electrocatalyst is composed of amorphous nanoparticles having tiny nanocrystals.

[0064] In one embodiment, the ruthenium-based electrocatalyst may further include a manganese oxide (MnO x ) Carbon black powder in the support.

[0065] In various embodiments, the ruthenium-based electrocatalyst further comprises a substrate, wherein the ruthenium oxychloride species and the manganese oxide support are dispersed in the substrate. In various embodiments, the substrate is porous, mesoporous or microporous. Examples of suitable substrate materials include, but are not limited to, any carbon-based porous material, including carbon cloth, carbon cloth covered with a thinner microporous layer composed of carbon black powder, carbon fiber paper composed of carbon black powder, macroporous carbon fiber paper, carbon nanotube film and graphene film, and other carbon-based materials with mesoporous structure and good conductivity. In one embodiment, the substrate is carbon fiber paper.

[0066] The structure of the electrocatalyst disclosed in the present invention is in the form of manganese oxide (MnO x ) supports, it helps to destroy the Ru-O-Ru bonding structure in the ruthenium oxide (RuO2) crystal structure, thereby improving the stability of ruthenium-based catalytic materials. y ) species dispersed in MnO x The stability is further enhanced with the assistance of the Ru-O-Mn bond formed in the support. The electrocatalyst is constructed through rational catalyst system design and appropriate support material selection, as well as material fabrication and structural optimization for catalytic performance and catalytic mechanism in the acidic oxygen evolution reaction (OER), with special attention paid to the intrinsic relationship between support type, material system energy, interface bonding and catalytic stability enhancement.

[0067] By uniformly dispersing ruthenium in MnO x The formation of ruthenium oxide (RuO2) crystals is avoided in the bulk phase of the support, and the structure of the electrocatalyst also helps to improve the oxidant potential of the ruthenium catalyst system.

[0068] The halogen element of the ruthenium-based electrocatalyst helps to improve the stability of the electrocatalyst. In one embodiment, the halogen element is chlorine (Cl). In other embodiments, the halogen element can be fluorine (F) or bromine (Br).

[0069] The present disclosure also provides a method for manufacturing a ruthenium-based electrocatalyst. In obtaining the method of the present disclosure, methods such as low-temperature one-step annealing method, multi-step annealing method and rapid high-temperature sintering method have been explored. The method is obtained by adjusting the temperature process parameters, the metal ratio of the ruthenium-based electrocatalyst, the ligand structure of the ruthenium-based electrocatalyst, the crystallization difference and the crystallinity of the ruthenium-based electrocatalyst. The method allows the mass loading of ruthenium to be minimized without significantly affecting its activity.

[0070] See also Figure 1 The method includes heating a substrate and applying a precursor solution containing a chloride salt of ruthenium and a nitrate salt of manganese to the substrate. The precursor solution and the substrate are then heated at a temperature for a predetermined time to obtain a substrate having a general formula of MnO dispersed therein. x The manganese oxide support having the general formula RuOCl y In various embodiments, y represents a number between 0.2 and 1.6, and x represents a number between 1.7 and 1.8.

[0071] In various embodiments, the chloride salt of ruthenium is ruthenium(III) chloride (RuCl 3 ), and the nitrate salt of manganese is manganese(II) nitrate (Mn(NO 3 ) 2 ).

[0072] Ruthenium oxychloride (RuOCl y ) species is bonded to manganese oxide (MnO x ) oxygen atoms in the support to form a dominant Ru-O-Mn, and after oxidation of the RuCl3 precursor, the remaining Cl element is doped or chemically adsorbed on the electrocatalyst body or micropores. The doped / chemically adsorbed chlorine promotes the dispersion of ruthenium atoms and thus provides a large number of active structural defects. The defect structure caused by ruthenium atoms is introduced into the solid MnO x The active ruthenium atoms are surrounded by a large number of manganese and oxygen atoms, which induces a protective effect on the catalytic sites. This geometric structure of the electrocatalyst has several advantages, including similar octahedral coordination in the crystal phases of ruthenium oxide (RuO2) and manganese oxide (MnO2), which makes RuOCl@MnO xThe materials have a compatible unit structure, thus suppressing the tendency of phase segregation. Another advantage is the amorphous nature of the electrocatalyst caused by low-temperature synthesis, which increases the density of defect sites such as grain boundaries and edges, thereby improving the catalytic activity. Another advantage is that MnO x Used as a support. MnO x The material has excellent acid corrosion resistance and oxidation resistance, and this provides a reliable and stable support for ruthenium-based electrocatalysts, thereby destroying the agglomeration of ruthenium oxide (RuO2) and improving the oxidation potential. The electrocatalyst has excellent stability in the acidic oxygen evolution reaction, which is achieved by ruthenium in a stable MnO x The dispersion in the support is significantly enhanced. x The support has strong acid and oxidation resistance, and this helps to stabilize the enclosed ruthenium species (Ru species) by suppressing the formation of ruthenium oxide (RuO2).

[0073] The active Ru sites significantly reduce the overpotential of the oxygen evolution reaction and thus slow down the reaction from MnO x The support is oxidized to MnO at a higher potential. 4- The resulting MnO x Deterioration of the support. The active ruthenium sites are in MnO x The uniform dispersion in the support or matrix leads to a more active and sustained oxygen evolution reaction at a lower ruthenium mass loading. This helps to reduce the manufacturing cost and product cost of the electrocatalyst. In addition, RuO2 and MnO2 with strong catalyst-support interaction are more active in the oxygen evolution reaction. x The two work synergistically to enhance the overall catalytic performance. The resulting electrocatalyst exhibits 10 mA cm -2 The lower overpotential of 228 mV in strong acid medium (0.5 M sulfuric acid, pH 0.26) was 10 mA cm -2 280 h at 100 mA cm -2 Excellent stability of 200 hours, and 0.105 mg Ru / cm -2 The invention discloses a ruthenium-based electrocatalyst having a lower ruthenium loading than most reported ruthenium-based oxygen evolution reaction electrocatalysts. The electrocatalyst can be applied to proton exchange membrane (PEM) electrolyzers. In PEM electrolyzers, the ruthenium-based electrocatalyst can achieve higher energy conversion efficiency than existing ruthenium / iridium (Ir)-based catalysts. When the electrocatalyst is used in a PEM electrolyzer, the electrocatalyst has a higher water electrolysis current density than existing ruthenium / iridium-based catalysts.

[0074] In various embodiments, the substrate and the precursor solution are heated to a temperature in the range of 200° C. to 220° C., preferably in the range of 205° C. to 215° C., more preferably 210° C. In various embodiments, the substrate and the precursor solution are heated for a period of time sufficient to form a ruthenium oxychloride species (RuOCl y species) and manganese oxide (MnO x ) supports, and avoid the formation of a highly crystalline phase, and thus retain a large number of defects. In various embodiments, the substrate and the precursor solution are heated for a period of time between 8 minutes and 20 minutes, preferably a period of time between 8 minutes and 12 minutes, and more preferably a period of time between 8 minutes and 10 minutes.

[0075] In various embodiments, the substrate is porous, mesoporous or microporous, and the ruthenium oxychloride species and the manganese oxide support are dispersed in the substrate. Examples of suitable substrate materials include, but are not limited to, any carbon-based porous material, including carbon cloth, carbon cloth covered with a thinner microporous layer composed of carbon black powder, carbon fiber paper composed of carbon black powder, carbon nanotube film, graphene film, and other carbon-based materials with mesoporous structure and good conductivity. In one embodiment, the substrate is carbon fiber paper.

[0076] The method of the present disclosure is simple, cost-effective, and scalable.

[0077] According to another aspect, the present disclosure provides a membrane electrode for a proton exchange membrane electrolyzer. The membrane electrode comprises a porous substrate and a porous substrate having a general formula of MnO x The manganese oxide support having the general formula RuOCl y The invention relates to a ruthenium oxychloride species, wherein the ruthenium oxychloride species and the manganese oxide support are dispersed in the porous substrate. In various embodiments, y represents a number between 0.2 and 1.6, and x represents a number between 1.7 and 1.8. In one embodiment, the substrate is a carbon fiber paper.

[0078] In order to better understand the present application, the following examples of specific embodiments are given. The following examples should not be considered as limiting or defining the full scope of the present application. Those skilled in the art will recognize that the examples shown below are not an exhaustive list of embodiments of the present application.

[0079] Example

[0080] Example 1 - Fabrication of Ruthenium-based Electrocatalysts

[0081] In this example, carbon fiber paper (CFP) is used as the substrate. It will be appreciated that other types of substrates may be used without departing from the scope of the present disclosure.

[0082] First, the carbon fiber paper was prepared before use. The carbon fiber paper was ultrasonically cleaned using acetone, ethanol, and deionized water in sequence, and then the carbon fiber paper was hydrophilized by heating at 250° C. for 30 minutes before use.

[0083] RuOCl@MnO x The samples were fabricated by a one-step heating treatment method, where 0.5 mg of RuCl3·xH2O powder and 15 μL of 2.15 M Mn(NO3)2 solution were first dissolved in 1 ml of deionized water by stirring at room temperature to form a precursor solution. The precursor solution containing ruthenium(III) chloride (RuCl3) and manganese(II) nitrate Mn(NO3)2 was then dropwise applied onto the surface of 1 cm² of carbon fiber paper, which had been first heated at 210°C on a hot plate. The carbon fiber paper loaded with the precursor solution was then heated again at 210°C for 10 minutes and then rinsed thoroughly with water. Due to the porous structure and hydrophilic surface of the carbon fiber paper, about 46% of the solution (by comparing the mass increase after heated deposition between the carbon fiber paper substrate and the underlying quartz spacer) was deposited on the carbon fiber paper substrate. This corresponds to 0.23 mg cm -2 The loading mass of RuCl3·xH2O precursor is obtained. x RuOCl in the support y Species of ruthenium-based electrocatalysts (RuOCl@MnO x ). Due to its excellent acid and oxidation resistance, the carbon fiber paper substrate supported with ruthenium-based electrocatalyst is suitable for the fabrication of membrane electrode assemblies for proton exchange membrane (PEM) electrolyzers. Notably, the fabrication method is scalable because it uses mild synthesis conditions and lower-cost manganese oxide (MnO2) as a support.

[0084] Schematic electrocatalyst structure Figure 2 , where the ruthenium oxychloride species (RuOCl y species) dispersed in manganese oxide (MnO x ) in the supporting body.

[0085] The same heating method was also used to prepare a separate RuCl3·xH2O solution or Mn(NO3)2 solution that was dropped onto the substrate to obtain RuOCl or MnO, respectively. x As another control sample, RuOCl / MnO xThe RuCl3·xH2O solution was also applied dropwise to the prepared MnO x The same heating procedure was followed on the samples.

[0086] For the commercial RuO2 catalyst sample, 4 mg of RuO2 was applied to 1 ml of a water / ethanol (volume ratio 3:1) solution containing 20 μl of Nafion solution (5%, DuPont D520) and dispersed by ultrasound for 1 hour to generate a uniform ink. Then 38 μL of the ink was dropwise applied to a 1 cm² carbon fiber paper substrate to achieve a RuO2 loading mass of 0.15 mg (denoted as RuO2|0.15@CFP), which corresponds to the same as RuOCl@MnO x The atomic mass of ruthenium in the same ruthenium is the same as that of ruthenium in the MnO, and the drip-drying cycle produces a higher loading mass. The obtained products are recorded as RuO2|x@CFP (x=0.15, 0.3, 0.45, 0.6, 0.75, 0.9, 1.05). In addition, 0.15 mg (38 μL) of RuO2 was dripped into the synthesized MnO x , denoted as RuO2 / MnO supported by carbon fiber paper x Working electrode.

[0087] Example 2

[0088] Various characterization tools are used to study the dispersion properties of the ruthenium atoms, the elemental valence state, the degree of segregation, as well as the crystallinity and particle morphology of the support oxide.

[0089] X-ray diffraction (XRD) analysis was performed and the results were as follows Figure 3 XRD structural analysis shows that (A) RuOCl@MnO x and (C) the amorphous state of RuOCl, as indicated by the absence of well-defined peaks. For (B) MnO x The XRD peaks at 2θ=33.1°, 55.2° and 66.0° correspond to the (222) plane, (440) plane and (622) plane of the Mn2O3 structure, respectively. (A) RuOCl@MnO x The absence of the crystalline peaks in MnO indicates that the applied Ru interferes with x The crystallinity of the support is attributed to the disordered bonding and doped / chemisorbed chlorine atoms. It is noteworthy that the crystal defects and unsaturated coordination sites in RuO2 catalysts are responsible for the highly active oxygen evolution reaction. Figure 4 The Raman spectra shown show (A) RuOCl@MnO xThe peak position is close to (B) MnO x The peak position of 505 cm -1 、566 cm -1 (Mn-O stretching vibration in the basal plane) and 643 cm -1 (Symmetric stretching mode of MnO6 cluster) corresponds to the lattice vibration mode of MnO2. (C) The RuOCl sample does not show the lattice vibration peaks observed in crystalline RuO2. Therefore, it is not possible to form crystalline RuO2 from an aqueous ruthenium(III) chloride (RuCl3) precursor by treating it at 210°C for 10 minutes, whereas crystalline MnO2 can be obtained by thermal decomposition of Mn(NO3)2 under this condition. x .

[0090] The elemental composition of Ru 3p state, Cl 2p state, Mn 2p state and O 1s state was analyzed by X-ray photoelectron spectroscopy (XPS). Figure 5 The XPS spectrum shown covers the catalyst (A) RuOCl@MnO x and Ru, O, and Cl in the catalyst (B) RuOCl, and from (C) MnO x Mn and O elements of the support. Ru 3p peaks at 463.8 eV and 486.2 eV ( Figure 6 ), and the Ru 3d peaks at 281.3 eV and 285.5 eV ( Figure 7 ), which is marked at Ru 4+ It should be noted that even at the same ruthenium loading, RuOCl@MnO x The intensity of Ru in MnO is much lower than that in RuOCl, which indicates that Ru is present in MnO x It is worth noting that in (A) RuOCl@MnO x Significant chlorine signals were observed in both (A) and (B) RuOCl. Figure 8 ), the chlorine signal is located at 198.1 eV and 199.8 eV and corresponds to Cl - Cl 2p 3 / 2 and Cl 2p 1 / 2 Even though the fabricated samples were thoroughly washed, the chlorine was not completely removed, which indicated that the chlorine element had been doped or firmly chemically adsorbed on the bulk or micropores of the electrocatalyst.

[0091] In addition, the O 1s spectrum ( Fig. 9 ) can be deconvoluted into lattice oxygen (529.7 eV), hydroxyl / CO / adsorbed oxygen on the surface (531.2 eV).

[0092] In (A) RuOCl@MnO x and (B) MnO x The Mn 2p at 641.7 eV and 643.6 eV 3 / 2 Signal( Fig.10 ), are marked as Mn 3+ State and Mn 4+ state, among which RuOCl@MnO x The ratio is about 1.8 (Mn 3+ :Mn 4+ ). Through semi-quantitative analysis of XPS ( Fig.11 ), RuOCl@MnO x The ratio of Ru:Cl:O:Mn in RuOCl is 1:0.8:15.5:7.8, which indicates that each ruthenium catalytic site is surrounded by 8 manganese atoms to ensure its good dispersion. In contrast, the chlorine content is significantly lower in RuOCl, which has a Ru:Cl:O ratio of 1:0.2:2.1, which indicates that some chlorine can be doped or chemisorbed on MnO. x Combined with XRD analysis, MnO x The ratio of Mn:O in the x The support contains a mixture of polycrystalline Mn2O3 and amorphous MnO2.

[0093] The K-edge XANES spectra were analyzed by fitting the oxidation states of Ru / Mn as a function of the Ru / Mn K-edge energy shift (Figure 12) to further confirm the oxidation states of Ru and Mn, and the calculated average valence states of Ru and Mn were Ru +3.9 and Mn +2.8 .

[0094] The high resolution transmission electron microscopy (HRTEM) image in Figure 13(a) shows that RuOCl@MnO x It is composed of amorphous nanoparticles with tiny nanocrystals, and the interplanar spacing (d-spacing) of 0.27 nm corresponds to the (222) plane of Mn2O3. In addition, the obtained SAED pattern shown in Figure 13 (b) shows weak diffraction rings corresponding to the (222) plane, (411) plane, (521) plane, and (622) plane of Mn2O3, which further indicates that RuOCl@MnO x The absence of RuO2 nanocrystals indicates that ruthenium is present in MnO xIn addition, the image taken by Aberration-Corrected High-Angle Annular Dark Field Scanning Transmission Electron Microscopy (AC HAADF-STEM) (Figure 13(c)) shows that some individual Ru atoms, as shown by the distinguishable bright spots marked by multiple circles, are well dispersed in the MnO x On the surface of the support. RuOCl@MnO x The element distribution in the electrocatalyst was obtained from the images of Scanning Transmission Electron Microscopy with Energy Dispersive X-ray Spectroscopy (STEM-EDS), and the results shown in Figures 13 (d) to (h) show that all elements including Ru, Cl, O and Mn are uniformly distributed in the electrocatalyst. Ru K-edge k 2 The Fourier transforms (FTs) of the χ(k) spectra (Figure 13(i)) show that the Ru-O peak shifts from 1.50 Å of (B) RuO2 to 1.50 Å of (A) RuOCl@MnO x 1.57 Å, which is attributed to RuOCl@MnO x The dominance of the Ru-O-Mn bond in the Mn K-edge leads to a change in the local coordination environment. The absence of the Ru-Cl peak indicates that Ru-Cl is completely converted to Ru-O during the thermal synthesis process. 2 Fourier transform of the χ(k) spectrum, where 1.5 Å, 2.4 Å, and 3.0 Å match the Mn-O bonds in the MnO6 octahedron, the edge-sharing Mn-Mn edge and corner-sharing Mn-Mn corner , indicating that despite the introduction of external elements, according to the Raman results, MnO x The MnO6 octahedral framework in the support is still maintained. The missing Ru-Cl bonds and Mn-Cl bonds are consistent with the doping or adsorption state of chlorine in the catalyst. In addition, compared with the obvious Ru and Cl peaks in RuOCl, Fig.14 The EELS images shown only show the RuOCl@MnO sample. x The absence of Ru and Cl peaks caused by the weakening of the signal due to the surrounding of the manganese oxide support indicates that RuOCl has beenx Evenly dispersed in the matrix rather than agglomerated on the surface. Fig.15 The SEM images shown show that RuOCl@MnO x and MnO x Both were densely deposited on the carbon fiber paper (CFP) surface, however, RuOCl showed poor coverage. The element content was quantified using SEM-EDS analysis, and the results are shown in Figure 16. The results show that Ru, Cl, O, and Mn are uniformly distributed on the deposited film. The RuOCl@MnO obtained from EDS x The ratio of Ru:Cl:O:Mn in RuOCl (1:1.6:18.0:11.1) (see Figure 13(k)) and the ratio of Ru:Cl:O in RuOCl (1:0.4:2.4) (see Figure 13(l)) show that the percentage of chlorine measured by EDS is higher than that measured by XPS, indicating that more chlorine has been doped or chemically adsorbed below the surface. In addition, the ratio of Mn:O measured by EDS (1:1.7) is close to the ratio obtained by XPS spectrum, which indicates the presence of a mixture of polycrystalline Mn2O3 and amorphous MnO2. RuOCl@MnO x The mass loading of ruthenium in the - ² (Based on the molecular weight of RuCl3·H2O = 207.43 g mol -1 Calculation) or 0.105 mg cm - ² (based on inductively coupled plasma (ICP) testing), which corresponds to 0.15 mg or 0.14 mg of initial RuO2, respectively.

[0095] Example 3

[0096] The RuOCl@MnO x The results of Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) were obtained. A piece of carbon fiber paper (CFP) supported RuOCl@MnO x (1 cm 2 ) was placed in 10 mL of concentrated hydrochloric acid at 60 °C for 20 min, and the solution was then transferred to a 250 mL volumetric flask to be diluted with 0.23 mol L -1 The blank sample of pure carbon fiber paper was treated in the same way. The results are shown in Table 1.

[0097] Table 1

[0098]

[0099] The results were obtained at 10 mA cm -2 , 100 mA cm -2 , 300 mA cm -2 and 500 mA cm -2 ICP-OES results of the electrolyte (50 mL) after 280 hours, 200 hours, 100 hours, and 50 hours of chronopotentiometry. The acidity was adjusted using 0.23M nitric acid and the ion concentrations were converted to be close to those dissolved in the initial electrolyte. The blank samples were treated in the same way, but no chronopotentiometry was performed, and the results are shown in Table 2.

[0100] Table 2

[0101]

[0102] Ruthenium deposition on the cathode platinum (Pt) wire was observed after long-term testing, and the ruthenium was returned to the solution by applying a higher voltage (2V) for a shorter time (30 s) to obtain a shiny platinum wire and a more accurate ion concentration. It is worth noting that the ruthenium deposited on the cathode platinum has no significant effect on the anodic oxygen evolution reaction process studied in this paper.

[0103] ICP-OES also shows that RuOCl@MnO x The ratio of Ru:Mn in RuOCl@MnO is 1:9.6, which is close to the ratio estimated from EDS or XPS analysis. Table 3 is a summary of the atomic ratios obtained from XPS / EDS / ICP-OES. x The atomic concentrations in the samples and RuOCl were normalized to the concentration of Ru, and in the MnO x In the equation, the atomic concentration is normalized to the manganese concentration.

[0104] Table 3

[0105]

[0106] Example 4

[0107] Electrochemical tests were performed to evaluate the stability and activity of the electrocatalysts of the present disclosure.

[0108] The electrochemical performance tests were performed on an electrochemical workstation (model CHI 660E) with a standard three-electrode setup in an electrolyte of 0.5 M H2SO4 purged with oxygen. x Samples, RuOCl samples, MnO xSample, RuOCl / MnO x Sample, RuO2 / MnO x The samples and RuO2|x@CFP samples were used as working electrodes. Ag / AgCl (saturated KCl) electrode and platinum wire were used as reference electrode and counter electrode, respectively. All linear sweep voltammetry (LSV) curves were obtained at 5 mV s -1 The potential scan rate was recorded and the chronopotentiometry was performed at 10 mA cm -2 , 100 mA cm -2 , 300 mA cm -2 and 500 mA cm -2 For the geometric area used for electrochemical linear sweep voltammetry (LSV) measurements, for 10 mA cm -2 and 100 mA cm -2 The chronopotentiometry geometry is 1 cm² and is used for 300 mA cm -2 and 500 mA cm -2 The area is 0.5 cm². RuO2|0.15@CFP, RuOCl@MnO x and MnO x The test areas of the LSV curves extended to higher positive potentials were 1 cm², 0.5 cm², and 0.5 cm², respectively, and the potential scan rate was 0.1 mV s -1 . After full iR correction (manual iR compensation, where R s The full potential (obtained from the EIS results at open circuit voltage) is converted to the reversible hydrogen electrode (RHE) scale if not mentioned separately, i.e., E(RHE) = E(Ag / AgCl) + 0.197 V + 0.059 × pH.

[0109] Stability tests were performed and the results are shown in Figure 17(a), which shows the -2 The potential change under constant oxygen evolution reaction current density. RuOCl@MnO x The catalyst exhibited stable operation for up to 280 h, with only a 50 mV drop in overpotential, corresponding to a 0.18 mV h -1The degradation rate of (D) RuO2|1.05@CFP and (E) RuO2|0.15@CFP (having 1 and 7 times the activity of RuOCl@MnO2, respectively) is shown in Table 17. It is worth noting that most of the degradation (46%) occurs within the first 25 hours (inset of Figure 17(a)). This excellent stability is superior to most ruthenium-based oxygen evolution reaction electrocatalysts operating in acidic media. In contrast, both the initial RuO2 and the initial RuOCl exhibit rapid activity degradation. Specifically, (D) RuO2|1.05@CFP and (E) RuO2|0.15@CFP (having 1 and 7 times the activity of RuOCl@MnO2, respectively) show a very fast degradation rate. x (A) The potential of RuOCl increases from 1.44 V to 2 V in 4 h, which corresponds to 140 mV h -1 In addition, (C)MnO x The relative steady-state oxygen evolution reaction potential of MnO deteriorates from 1.86 V to 1.93 V within 20 hours. This shows its strong antioxidant capability but poor oxygen evolution reaction activity. These comparative data indicate that Ru is the active site and MnO x plays the role of supporting material, which gives RuOCl@MnO x In addition, it should be noted that compared with the rapid deactivation of (B) RuOCl (within 4 h) and (E) RuO2|0.15@CFP (within 0.05 h), the rapid deactivation of (F) RuOCl / MnO x Potential and (G)RuO2 / MnO x The potential of α-MnO undergoes a significantly slower decrease to 1.54 V and 1.79 V within 30 h and 20 h, respectively, which means that even by simply supporting MnO x On the surface of MnO x It can also stabilize the electrocatalyst. RuOCl / MnO x and RuO2 / MnO x The enhanced durability can be attributed to the oxygen evolution reaction process of MnO x However, the inhomogeneous and uncontrollable dynamic surface reactions make RuO2 / MnO x Compared with RuOCl@MnO x The activity is weak.

[0110] It will be noted that the term "RuOCl / MnO x ” refers to the dispersion in manganese oxide (MnO x ) Ruthenium oxychloride species (RuOCl species) in the support, wherein the RuOCl species is mixed with MnO x No chemical bonds are formed between the supports.

[0111] The term "RuO2 / MnO x ” refers to the dispersion in manganese oxide (MnO x ) RuO2 species in the support, wherein RuO2 species and MnO x No chemical bonds are formed between the supports.

[0112] The operation of the steady-state oxygen evolution reaction at higher current density accelerates the oxidative failure of the electrocatalyst and is therefore an important consideration for practical applications. -2 , 300 mA cm -2 and 500 mA cm -2 The stability of the electrocatalyst was tested at a higher current density of 100 mA cm -2 After 200 h of continuous operation, the overpotential increase was 115 mV. This corresponds to 0.6 mV h -1 Degradation rate at 300 mA cm -2 (at a degradation rate of 164 mV in 100 h) and 500 mA cm -2 The degradation rate is accelerated by 346 mV in 50 hours.

[0113] Then, the electrocatalyst RuOCl@MnO was evaluated using linear sweep voltammetry (LSV) curves. x activity (Figure 17(c)). RuOCl@MnO x At an onset potential of 1.42 V (and 10 mA cm -2 In contrast, the onset potentials of (C) RuO2|0.15@CFP and (D) RuO2|1.05@CFP are significantly higher at 1.52 V and 1.48 V, respectively. -2 At a current density of , the overpotential of RuO2|1.05@CFP is 306 mV ( Fig.18 At 1.6 V, RuO2|1.05@CFP and RuO2|0.15@CFP exhibit 32 mA cm -2 and 5 mA cm -2 The smaller current density (compared to RuOCl@MnO x 118 mA cm -2 In addition, for MnO x , a higher onset potential of 1.77 V and at 10 mA cm -2The higher overpotential of 620 mV also indicates that the active sites are not derived from MnO x In addition, RuOCl suffers from rapid degradation in potential sweep tests ( Fig.19 ). It should be noted that the x The same mass of ruthenium loaded on RuO2|0.15@CFP (based on the molecular weight of RuCl3·H2O = 207.43 g mol -1 Calculated), when driving 10 mAcm -2 At a current density of 2.5 Å, the overpotential is much higher than 306 mV. As the ruthenium loading gradually increases (see Figure 20 (a)), the overpotential of RuO2|0.15@CFP reaches 306 mV, which is close to the overpotential of RuO2 supported on a glassy carbon electrode (about 0.275 mg cm -2 ). The poor performance is attributed to the supported RuO2 nanoparticles (TEM image shown in Figure 20(b)) being partially stuck in the inter-fiber voids of the carbon fiber paper and thus unable to participate in the catalytic reaction efficiently. (A) RuOCl@MnO x The mass activity ( Fig.21 ) up to 481 A g at η = 300 mV Ru 1 , which is 41 times higher than the mass activity of (C) RuO2|1.05@CFP or (B) RuO2|0.15@CFP ( Fig.18 ), which indicates that RuOCl@MnO x It is one of the most excellent low-mass supported ruthenium-based and iridium-based electrocatalysts. It is worth noting that see Fig. 22 , (A) RuOCl@MnO x Tafel curves (43 mV dec -1 ), lower than (B) RuO2|0.15@CFP (48 mV dec -1 ) and (C)RuO2|1.05@CFP (53 mV dec -1 ), which indicates faster oxygen evolution reaction kinetics.

[0114] The structural stability of the electrocatalyst was investigated after a 280-hour stability test. Fig.23 (a) to (c)), after stability testing, the electrocatalyst showed a nanosheet structure similar to that of MnO2 (see Fig.23 (d) to (f)). Fig.26 As shown in (a), multiple Raman peaks are slightly shifted to 497 cm-1 、572 cm -1 、651cm -1 , which can be attributed to the change of valence state and bond length. The new -1 The peak corresponds to the bending vibration mode of Mn-O-Mn. Fig.24 The XRD pattern in Figure 1 does not show any peaks of crystalline MnO2, which indicates that the amorphous phase of MnO2 is dominant. By HRTEM, some tiny nanocrystals with a lattice spacing of 0.36 nm can still be observed ( Fig.25 ), the lattice spacing of 0.36 nm corresponds to the (002) plane of δ-MnO2, which indicates that MnO x Transformation of the support during the catalytic process. RuOCl@MnO after 48 hours of testing x XPS spectra and normalized Ru K-edge XANES spectra ( Fig.26 (b to c) show that there is no significant degradation of the Ru active sites in the early stages of long-term catalysis. After 48 hours of testing, the Mn K-edge XANES spectrum changes from close to Mn2O3 (Mn 3+ energy toward MnO2 (Mn 4+ At the same time, a significant positive shift of the Mn 2p peak was observed by XPS after 280 hours (see Fig.26 (d) to (e). At the same time, Mn 3+ / Mn 4+ The ratio of 1.8 (initial) gradually decreased to 1.1 (after 280 h), which further indicated the increase of MnO2, which was consistent with the morphology and Raman characterization. Fig.26 (f)) is closely related to the degradation of the electrocatalyst. Significant degradation occurs after 280 hours, as the Cl peak disappears after 280 hours of testing. In addition, the O 1s peak of lattice oxygen (see Figure 27 (a)) shifts slightly after 280 hours of testing, which can be attributed to the composition, valence state, and microstructure of the redeposited MnO2 nanosheets. After the 280-hour stability test, the weights of manganese and ruthenium ions dissolved in the solution were 0.08 mg and 0.07 mg, respectively. However, other dissolved Mn 3+ redeposited on the surface in the form of MnO2 nanosheets (see Fig.23 and Fig.25). Notably, the high activity of the electrocatalyst was not significantly affected during the redeposition process, and the Faradaic efficiency (charge involved) of the Mn / Ru ion reaction was negligible compared to that of the oxygen evolution reaction or the hydrogen evolution reaction (HER). Moreover, sheet-like structures with morphological changes depending on the applied potential were observed after stability testing at higher current densities. Fig.28 is (a to c) at 100 mA cm -2 After 200 h stability test under 300 mA cm -2 After 100 h stability test under 500 mA cm -2 RuOCl@MnO after 50 hours stability test x SEM images and SEM-EDS full element distribution diagrams. x As shown in the HRTEM image, the flakes are mainly composed of amorphous phase, such as Fig.29 shown. Fig.30 The Raman peak shown is slightly shifted, with a peak at 385 cm -1 (bending vibration of Mn-O-Mn) and 720 cm -1 The appearance of multiple peaks of (Mn-O-Mn stretching vibration). In addition, the Ru 3p peak is significantly weakened, and the Mn 2p peak and O 1s peak show similar positive shifts (see Figure 31). As shown in ICP-OES characterization, manganese ions and ruthenium ions dissolve faster at higher positive potentials (anodic potentials) (see Table 3).

[0115] MnO2 and RuO2 corrode through the following reactions:

[0116] ,as well as

[0117] .

[0118] In the durability test, the MnO x The catalyst support remains stable in the range of 1.86 V to 1.93 V for at least 20 h (Fig. 17(a), curve C). The calculated Pourbaix diagram of the 89-11% Mn-Ru system in aqueous solution ( Fig.32 ) also shows that the oxidation potential of MnO2 is higher than that of RuO2. A slower scan (0.1 mV s -1) LSV test, and the results are shown in Figure 33. The results show that the oxygen evolution reaction dominates before the catalyst deteriorates, and significant degradation occurs at the obvious inflection point of the oxygen evolution reaction current. x and MnO x The potentials at the inflection points are 1.76 V, 2.49 V, and 2.55 V, respectively. It can be seen that MnO x The support greatly improves the RuOCl@MnO x Oxidation potential of the electrocatalyst. It is noteworthy that elevated oxidation potential is crucial for enhanced stability. The dissolution of the RuO2 lattice, triggered by the loss of lattice / surface oxygen with the sharing of oxygen evolution reaction intermediates, depends on the applied potential and is significantly higher when the potential is well above the theoretical redox potential (1.39 V RHE , pH 0), the dissolution of RuO2 lattice will be more serious. x The dispersion in the support leads to a higher oxidation potential of the electrocatalyst and thus enables long-term stability even at higher current densities.

[0119] Given the predominantly amorphous nature of the electrocatalyst, the catalytic reaction can involve the participation of lattice / surface oxygen. Unlike the Ru-O-Ru bonds in conventional RuO2, the Ru-O-Mn bonds here dominate (Figure 13(i)) because the ruthenium atoms are surrounded by up to ten times more manganese atoms. Due to the differences in bond length, electronegativity, and bond strength between Mn-O and Ru-O, RuOCl@MnO x The electrocatalysts differ from RuO2 in the recovery of the catalyst structure, such as oxygen vacancies. Oxygen vacancies involving lattice / surface oxygen accelerate the dissolution of RuO2, while the enhanced stability of the Ru catalyst is attributed to MnO x The presence of MnO x The structural recovery can be promoted and thus the degradation of the catalyst can be reduced. Therefore, the bulk formation energy and surface energy of the three models of RuO2, Mn2O3 and Mn2O3Ru were calculated (see Fig.34 ), because formation energy and surface energy are key parameters for evaluating structural stability.

[0120] Surface energy ( ) and formation energy ( ) is calculated by the following formula (1) and formula (2):

[0121]

[0122]

[0123] in, is the total energy per unit cell of the bulk phase, n is the number of unit cells contained in the slab model, and is the surface area of ​​the plate model. It is the bulk energy of each metal atom. It is half the energy of oxygen. and are the numbers of metal atoms and oxygen atoms in the bulk system, respectively.

[0124] It is worth noting that based on the XRD, HRTEM, XPS and Mn K-edge XANES analysis, it is shown that Mn 3+ Dominant, Mn2O3 is suitable as MnO x Simulation model of the support. In addition, since the doped / chemisorbed chlorine is not directly involved in the oxygen evolution reaction process, the doped / chemisorbed chlorine is not included in the model. As shown in Figure 33 (b), the formation energies of RuO2, Mn2O3 and Mn2O3Ru are -1.16 eV, -1.61 eV and -1.54 eV, respectively, while the surface energies are 1.30 eV, 0.65 eV and 0.73 eV, respectively. It is worth noting that both the bulk formation energy and surface energy of Mn2O3 are lower than those of RuO2, indicating that Mn2O3 is more stable than RuO2. In addition, even if 9% of Mn is replaced by Ru (i.e., Mn2O3Ru), the energy is still lower than that of RuO2, indicating that Mn2O3Ru has significantly improved structural stability compared to pure RuO2.

[0125] Figure 33(c) shows the calculated Gibbs free energy during the oxygen evolution reaction on different surfaces to evaluate the intrinsic activity. In this paper, the simulation model of Mn2O3Ru containing 9% ruthenium close to the experimental measured value and the simulation model of RuO2 were constructed as a benchmark, as shown in Figure 33(d). Ruthenium as the surface catalytic center has an unsaturated coordination structure, where Ru in RuO2 and Ru1 in Mn2O3Ru have a five-coordinated structure, and Ru2 in Mn2O3Ru has a four-coordinated structure, and these unsaturated sites are similar to the lattice / surface oxygen vacancies used for catalysis ( Fig.35 ). The present disclosure considers the adsorbate evolution mechanism (AEM). Since this is a four-electron transfer process, the energy of oxygen in the ideal catalytic process is estimated to be ΔG O2 = 4×1.23 = 4.92 eV. Comparing the Gibbs free energies on different surfaces, the reaction process of Ru2 site on Mn2O3Ru (110) surface is closer to the ideal catalytic process than that of Ru1 site on pure RuO2 and Mn2O3Ru (110) surface, because the theoretical overpotentials of Ru2 site on Mn2O3Ru (110), RuO2, Ru1 site on Mn2O3Ru (110), and Mn site on Mn2O3Ru (110) surface are 0.75 V, 0.99 V, 1.11 V, and 1.32 V, respectively. For the tetracoordinated Ru2 site with a lower overpotential, the formation of O* from OH* is the rate-determining step (RDS), although the overpotential of Ru2 site is still higher than the measured overpotential because the effects of solution and temperature are not considered in the model. In contrast, the pentacoordinated Ru1 site is limited by the formation of O2 from OOH*, which is accompanied by a larger overpotential than RuO2. The largest overpotential of the Mn site also indicates its role as a supporting material. Overall, the improvement in activity is consistent with the RuOCl@MnO x This is related to the tetracoordinate unsaturated structure of ruthenium in the catalyst.

[0126] In the present disclosure described above, the catalytically active RuOCl species are dispersed in the low-cost MnO xIn the support, a stable ruthenium-based electrocatalyst is obtained, thereby obtaining a cost-effective, active, and stable oxygen evolution reaction electrocatalyst for acidic electrolytes. In an exemplary embodiment, the electrocatalyst exhibits a 10 mA cm-2 overpotential of 228 mV. -2 , 481 A g at an overpotential of 300 mV Ru -1 The mass activity of 43 mV dec -1 More importantly, the electrocatalyst has a Tafel slope of 10 mA cm -2 The catalyst exhibited excellent stability for 280 h at 100 mA cm -2 , 300 mA cm -2 and 500 mA cm -2 The stable operation was achieved for 200 hours, 100 hours and 50 hours respectively under synchrotron radiation and other characterizations. The excellent stability was attributed to the synergistic effect of the catalytic species and the support, among which MnO with strong acid resistance and strong oxidation resistance x The support increases the oxidation potential and slows down the oxidative corrosion of ruthenium. At the same time, the ruthenium active sites allow the oxygen evolution reaction to occur at a lower potential, thereby inhibiting the oxidation of MnO. x Corrosion of the support. RuOCl on MnO x The dispersion in the support increases the oxidation potential and reduces the bulk formation energy and surface energy. Therefore, the durability of the electrocatalyst is greatly enhanced. It is worth noting that the tetracoordinated Ru sites in the catalyst have a lower overpotential and therefore have a higher activity than pure RuO2 catalysts. The ruthenium-based electrocatalyst and its manufacturing method disclosed herein provide a new strategy to manufacture a stable, active oxygen evolution reaction electrocatalyst with a lower ruthenium load for a proton exchange membrane electrolyzer.

Claims

1. A ruthenium-based electrocatalyst comprising: With the general formula RuOCl y The ruthenium oxychloride species is dispersed in a manganese oxide support having a general formula of MnO x . 2 . The ruthenium-based electrocatalyst according to claim 1 , wherein y represents a number between 0.2 and 1.6, and x represents a number between 1.7 and 1.

8.

3. The ruthenium-based electrocatalyst of claim 2, wherein the ruthenium oxychloride species is chemically bonded to the manganese oxide support.

4. The ruthenium-based electrocatalyst according to claim 3, wherein the ruthenium-based electrocatalyst is RuOCl@MnO x .

5. The ruthenium-based electrocatalyst according to claim 1, wherein RuOCl y With MnO x The molar ratio is 1:11.1 or 1:7.

8.

6. The ruthenium-based electrocatalyst according to claim 1, wherein the ratio of Ru:Cl:O in RuOCl is 1:0.4:2.4 or 1:0.2:2.

1.

7. The ruthenium-based electrocatalyst according to claim 1, wherein MnO x The ratio of Mn:O in the alloy is 1:1.7 or 1:1.

8.

8. The ruthenium-based electrocatalyst according to claim 1, further comprising carbon black powder dispersed in the manganese oxide support.

9. The ruthenium-based electrocatalyst according to any one of claims 1 to 8, further comprising a substrate, wherein the ruthenium oxychloride species and the manganese oxide support are dispersed within the substrate.

10. The ruthenium-based electrocatalyst according to claim 9, wherein the substrate is selected from the group consisting of carbon fiber paper, carbon cloth, carbon cloth covered by a thinner microporous layer consisting of carbon black powder, carbon fiber paper consisting of carbon black powder, macroporous carbon fiber paper, carbon nanotube film and graphene film.

11. The ruthenium-based electrocatalyst according to claim 10, wherein the substrate is carbon fiber paper.

12. A method for producing a ruthenium-based electrocatalyst, the method comprising: heating the substrate; applying a precursor solution containing a chloride salt of ruthenium and a nitrate salt of manganese to the substrate; as well as The precursor solution and the substrate are heated to obtain a ruthenium-based electrocatalyst, wherein the ruthenium-based electrocatalyst comprises a catalyst having the general formula RuOCl y The ruthenium oxychloride species is dispersed in a manganese oxide support having a general formula of MnO x .

13. The method of claim 12, wherein the precursor solution and the substrate are heated at a temperature ranging from 200°C to 220°C.

14. The method according to any one of claims 12 or 13, wherein y represents a number between 0.2 and 1.6, and x represents a number between 1.7 and 1.

8.

15. The method of claim 12, wherein the ruthenium oxychloride species and the manganese oxide support are dispersed within the substrate.

16. The method of claim 15, wherein the substrate is selected from the group consisting of carbon fiber paper, carbon cloth, carbon cloth covered by a thinner microporous layer consisting of carbon black powder, carbon fiber paper consisting of carbon black powder, macroporous carbon fiber paper, carbon nanotube film and graphene film.

17. The method of claim 16, wherein the substrate is carbon fiber paper.

18. A membrane electrode for a proton exchange membrane electrolyzer, the membrane electrode comprising: substrate, and dispersed on a substrate having the general formula MnO x The manganese oxide support having the general formula RuOCl y The invention relates to a ruthenium oxychloride species, wherein the ruthenium oxychloride species and the manganese oxide support are dispersed in the substrate.

19. The membrane electrode according to claim 18, wherein the substrate is carbon fiber paper.